DEMOKRATISASI DALAM PENEGAKAN HUKUM - Supriyanta - (Wacana Hukum, 2008)
Abstract :as one the elements of democracy, kaw should be the foundation of transparent, accountable and responsive governance, establishment of an honest and fair, general election system, protection of human rights and the existence of a democratic and contident society. Law should be able as well to guarantee  that the state administrators transparently do obey the rule of law in exercising their tasks. Law enforcement within a state should correspondent to the ideal of law of nation concerned. It means that the law enforcement should be in accordance with the philosophy, way of life, norms  and principles followed by the society concerned. Key word : Democracy. Law enforcement.